2011
DOI: 10.1002/jwmg.103
|View full text |Cite
|
Sign up to set email alerts
|

Development of an index of abundance for pygmy rabbit populations

Abstract: The pygmy rabbit (Brachylagus idahoensis) is a cryptic, burrowing lagomorph of conservation concern for which an efficient method to monitor populations is needed for conservation planning. We developed an index of abundance based on density of active burrow systems at 7 sites (57.2–118.5 ha) in east central Idaho. We conducted censuses of burrow systems and used mark‐resight surveys of 80 radio‐collared individuals to estimate density of rabbits. At 5 sites, we also used a second method to estimate rabbit num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In our system, pygmy rabbits were held at artificially high densities, well above the range described for wild populations. For example, Price and Rachlow (2011) documented a maximum density of 0.46 pygmy rabbits/ha in southeastern Idaho, compared with our range of 5-22 adult rabbits/ha. Consequently, these results should not be used to predict the response to changes in density of wild populations that are below carrying capacity.…”
Section: Reproductive Outputsupporting
confidence: 50%
“…In our system, pygmy rabbits were held at artificially high densities, well above the range described for wild populations. For example, Price and Rachlow (2011) documented a maximum density of 0.46 pygmy rabbits/ha in southeastern Idaho, compared with our range of 5-22 adult rabbits/ha. Consequently, these results should not be used to predict the response to changes in density of wild populations that are below carrying capacity.…”
Section: Reproductive Outputsupporting
confidence: 50%
“…(), who concluded that fresh sign could reliably index pygmy rabbit population trends. Indices of pygmy rabbit abundance have also been developed that are based on the density of active burrow systems, and have been found to be positively correlated with pygmy rabbit abundance (Price and Rachlow ). We used fresh pygmy rabbit sign to index trends across space rather than time, further negating any bias associated with temporal variation.…”
Section: Discussionmentioning
confidence: 99%
“…; Gruber et al . ; Johnson , Funston et al., ; Price & Rachlow ; Bengsen et al . ; Keane, Jones & Milner‐Gulland ), based on the assumption that detection probabilities may be constant or can be controlled for in some manner.…”
Section: Introductionmentioning
confidence: 98%
“…The thrust of these criticisms was that predictions about population size from such indices are obscured by the variation in detection rates of the indexing method over time or space. Despite strong criticisms, attempts to calibrate indices directly against estimates of absolute densities have continued persistently since 2005 (see Gusset & Burgener 2005;Stephens et al 2006, Barea-Azc on et al 2007Gruber et al 2008;Johnson 2008, Funston et al, 2010Price & Rachlow 2011;Bengsen et al 2011;Keane, Jones & Milner-Gulland 2011), based on the assumption that detection probabilities may be constant or can be controlled for in some manner.…”
Section: Introductionmentioning
confidence: 99%